Gênero no consumo de sagas fantásticas no Brasil - Xavier, Kellen do Carmo (2019)
Considering the popularization of fantastical fiction in the beginning of the 21st century, the dissertation aims to explore how the productive and symbolic dimensions of the structure of gender relations appear among the values that guide the consumption of these narratives in Brazil. Since the narrative structure of myth, one of the formal constituents of these fictions which we refer to as fantastical sagas, already provides for distinctions between men and women, the general objective of the work is to analyze the preferences of Brazilian fans of these sagas in order to identify which attributes are rejected and which endorsed by the research participants, and also which relationships we can establish between them and the socially established patterns of masculinity and femininity. To do this, we combined quantitative and qualitative analyzes of 247 answers from fans who answered the online survey questionnaire posted on Facebook. Among the results, we observed the preference for less stereotyped and passive considered female characters, in the face of a gender order that confers disadvantages to women in most societies - fictional or not - and the praise of attributes such as intelligence, independence, strength and courage, greater admiration when identified among women than among men.